Impact of An Evidence Based Prenatal Care Model on Patient Outcomes - Lynne Porter Lewallen PhD, RN, CNE; Cindy Jarrett-Pulliam RN, MSN, FACHE; Kelly Herger Dixon MSN, WHNP-BC (Journal of Primary Care & Community Health, 2010)
Health care providers face many challenges when providing prenatal care. This article reports on a program called Prenatal Care: the Beginning of a Lifetime (PCBL), to implement standardized prenatal care in central North Carolina. The purpose of this pilot study was to determine if there were differences in patient outcomes between a control group and 3 groups (A, B, and C) of increasing levels of intervention in standardized prenatal care. A total of 150 patients were enrolled and followed through delivery. There were no significant differences between the groups in cigarette smoking status, weight gain, genetic screening, sexually transmitted infection screening, diabetes screening, domestic violence assessment, 17P candidacy assessment, gestational age at delivery, or infant birth weight. However, a significant difference was found in depression screening. An association between intervention group membership and likelihood of being screened for depression was found in each trimester. As the level of intervention increased, the number of participants screened for depression increased significantly.